PEMBERDAYAAN POS PAUD DAN WAHANA DOLANAN MENDIDIK KARAKTER BAGI ANAK USIA DINI DI KABUPATEN MADIUN - Chasanatun, Fida; Wicaksana, Ervan Johan; Afifah, Sofia Nur (UNIVERSITAS PGRI MADIUN, 2016)
By years, children need a more complete educational stimulation, thus requiring additional educational services are conducted by environmental agencies and early childhood education at preschool. Stimulation education conducted in home (home base) and is done outside of home (center base) should be aligned and mutually supportive, in order to obtain maximal benefit. Outside education stimulation begins after baby 3 months or 6 months of aged. Unfortunately the service children of this age have a limited presence. If anything, not necessarily affordable to the community, both in terms of distance and cost. Post existence of early childhood as a form of early childhood kind Unit (SPS) is intended to bridge those needs. In the implementation of Post early childhood education can be integrated with a variety of early childhood services programs that already exist in the community such as: IHC, BKB (BKB), Parks Childcare (TPA), Play Group (PG). SPS program is intended for people who are not ready to engage her in a more intensive early childhood services, whether by reason of inconvenience escort, cost and other factors. Post early childhood education program will be implemented in some areas of Madiun regency that have not been getting early childhood education intensive and help parents to better know how to give good education to children at an early age period. The above options based on the need for early childhood education and have not been reached by the presence of intensive early childhood education in these areas. This program will also help parents to better know how to give good education to children at an early age period.